Humanitarian diplomacy as an instrument for China's image-building. Issue 3 (September 2021) - Gong, Lina
Image-building has been an important goal of China's foreign policy. Humanitarian diplomacy provides a useful instrument to build a benign international image, given the altruistic nature of humanitarian action. China's humanitarian diplomacy has undergone changes in recent years, such as substantial increases in humanitarian spending, institutional reforms and the emergence of Chinese non-state actors. The existing literature on China's humanitarian activities is scant due to the country's limited engagement in global humanitarian action previously. This article aims to contribute to the scholarship by examining China's humanitarian activities in Southeast Asia during the COVID-19 pandemic through the lens of image-building. Specifically, it answers the questions of how China uses humanitarian action to improve its international image and how effective such efforts have been. This article finds that the outcome of China's image-building through humanitarian activities is influenced by the severity of the crisis, the national response of the country affected and the perceived legitimacy of China's action. It concludes that China's humanitarian diplomacy has achieved mixed outcomes in Southeast Asia. While China has been recognized as a major provider of help during the pandemic, its assistance has not substantially improved its image in the region.